Genetic rhetorical criticism: An alternative methodology for studying multi-versioned rhetorical works. Issue 3 (2nd July 2016) - Jensen, Kyle
ABSTRACT: This essay presents genetic rhetorical criticism as an alternative methodology for the study of multi-versioned rhetorical works. In contrast to methodologies of textual authentication, which focus on the synchronic delivery of public address, genetic rhetorical criticism focuses on the diachronic movement of writing that both precedes and exceeds the work's introduction to public history. It does so by affirming the value of unauthorized versions of rhetorical works, which deepen the field's understanding of both particular rhetorical works and the textual dynamics of rhetoric. To support these claims, this essay reassesses the textual histories of both Abraham Lincoln's "Gettysburg Address" and Kenneth Burke's A Rhetoric of Motives . Engaging both works simultaneously shows that there are fundamental features of textuality that unite speech-centered and writing-centered rhetorical works. It also demonstrates that the textual histories of rhetorical works can support multiple scholarly interpretations.